MINAT PENGGUNAAN ELEKTRONIK BANKING BANK SWASTA DI YOGYAKARTA - Adityas Wahyuningsih; Arni Surwanti; Firman Pribadi (Universitas Multimedia Nusantara, 2019)
ABSTRACT Information systems and technology are increasingly developing. These developments have been utilized by banks to facilitate financial transactions by embarrassing innovation and implementing notional transactions, one of which is by implementing electronic banking. Research related to the analysis of factors that influence behavioral intention shows inconsistent results. Research related to the analysis of factors that influence interest and the level of using electronic private banks in Jakarta has never been done. This study aims to determine the factors that influence the interest and level of customer use using electronic banking services at Private Banks in Yogyakarta. The study was conducted with quantitative methods. Sampling is done by using an purposive sampling technique. Data is collected by a survey using a questionnaire. The study was conducted on 100 private bank customers in Yogyakarta who use electronic banking on November 2019. Data were analyzed using SEM-PLS analysis. The results show that effort expectations, perceived service quality, and hedonic motivation have a significant and positive effect on behavioral intention to use e-banking. Behavioral intention to use e-banking has a significant and positive effect on the level of e-banking usage. Performance expectations and social influence have no significant effect on behavioral intention to use e-banking. Keywords: behavioral intention, elektronic banking, intention to use, level of e-banking usage